Association and mediation between circulating inflammatory proteins and skin fibrosis - Zhao, Zirui; Lv, Dongming; Zeng, Ruixi; Rong, Yanchao; Xu, Zhongye; Yin, Rong; Hu, Zhicheng; Cao, Xiaoling; Tang, Bing (Frontiers in Endocrinology, 2025)
ObjectiveSkin fibrosis is a dermal lesion associated with inflammatory factors. However, the exact causal relationship between circulating inflammatory proteins (CIPs) and skin fibrosis remains unclear. To investigate this potential association and mediated effect, Mendelian randomization (MR) and two-step MR were used.MethodsSummary statistics from genome-wide association studies (GWAS) were extracted from the GWAS Catalog for CIPs, blood metabolites (BMs), and skin fibrosis. Two-sample MR and reverse MR were conducted to determine the effect of CIPs on skin fibrosis. Two-step MR was then performed to investigate the role of BMs in mediating the effect of CIPs on skin fibrosis. Reverse MR analysis was performed to confirm the unidirectional causality between CIPs and BMs, as well as between BMs and skin fibrosis.ResultsBidirectional Mendelian randomization revealed negative associations between skin fibrosis and the levels of T-cell surface glycoprotein CD6 isoform (odds ratio [OR] 0.670 [95% confidence interval [CI] 0.472, 0.951], p = 0.025), Delta and Notch-like epidermal growth factor-related receptor (OR 0.779 [95% CI 0.609, 0.998], p = 0.048), and Interleukin-10 receptor subunit beta (OR 0.541 [95% CI 0.332, 0.884], p = 0.014). There was a positive association between skin fibrosis and levels of Fibroblast growth factor 21 (OR 2.276 [95% CI 1.064, 4.870], p = 0.034). Two-step MR showed that Retinol (Vitamin A) to the linoleoyl-arachidonoyl-glycerol ratio (βM 0.108 [95% CI 0.006, 0.210], p = 0.004) and the Cholesterol to linoleoyl-arachidonoyl-glycerol ratio (βM 0.238 [95% CI 0.002, 0.474], p = 0.048) were identified as mediators, which showed evidence of the mediated effect of the levels of Fibroblast growth factor 21 on Keloid through these mediators.ConclusionThe study presented credible evidence of a causal association between CIPs and skin fibrosis, with BMs potentially acting as a mediator in this association. These findings offer new insights into early screening and prevention of skin fibrosis.